Effect of Growth Retardant ALARR on Some Anatomical and Chemical Changes in local Cultivar of Chrysanthemum morifolium - Nadia A El-Malki; A Barras – Ali (Scientific Journal of University of Benghazi, 2026)
The growth retardant ALAR was applied at different concentrations to study its effects on some anatomical and chemical Changes in growing stem cuttings of local cultivar of Chrysanthemum morifolium in terms of leaf area, leaf thickness and chlorophyll content in additions to measuring the ability of stem cuttings to resist drought conditions. The results showed that treated leaves were normal in shape but, a reduction in the leaves area have been achieved associated with darker green colour (high amount of chlorophyll Content) with respect to the ALAR concentrations applied. Treated plants showed some resistance to dry conditions.